The protective effects of Mirtazapine against lipopolysaccharide (LPS)-induced brain vascular hyperpermeability. Issue 2 (1st February 2022) - Pu, Yuehong; Zhao, Lei; Xi, Yao; Xia, Yichun; Qian, Yiming
ABSTRACT: Sepsis is mainly characterized by severe inflammation triggered by infection, and sepsis-associated encephalopathy (SAE) is defined as brain damage caused by sepsis. Disruption of the blood-brain barrier (BBB) triggered by injured brain microvascular endothelial cells (BMECs) and damaged tight junction (TJ) structure is closely associated with the pathogenesis of SAE. The present research proposed to evaluate the potential therapeutic effects of Mirtazapine, a central presynaptic α2 receptor antagonist, on LPS-induced BBB disruption. The mice were administered with normal saline and 10 mg/kg Mirtazapine for 8 consecutive days, and from day 6, the experiment group of mice received LPS for 2 days to induce SAE. We found that the increased BBB permeability, elevated concentrations of inflammatory factors in brain tissues, and downregulated zonula occludens −1 (ZO-1) were observed in LPS-stimulated mice, all of which were reversed by 10 mg/kg Mirtazapine. In the in vitro assay, bEnd.3 brain endothelial cells were treated with 1 μM LPS in the absence or presence of Mirtazapine (25, 50 μM). We found that LPS-treated cells had significantly declined transendothelial electrical resistance (TEER), increased monolayer permeability, elevated production of inflammatory factors, and downregulated ZO-1. However, 25 and 50 μM Mirtazapine ameliorated all these LPS- induced aberrations. Mirtazapine also mitigated the decreased level of NF-E2–related factor 2 (Nrf2) in LPS-challenged endothelial cells. The protective effect of Mirtazapine on endothelial permeability against LPS was significantly abolished by the knockdown of Nrf2. Collectively, we concluded that Mirtazapine exerted protective effects on LPS-induced endothelial cells hyperpermeability by upregulating Nrf2. GRAPHICAL ABSTRACT: uf0001